Pendidikan Kebencanaan perspektif Kisah Yusuf: Telaah Ayat 46-60 - Agus Firmansyah; Rio Kurniawan; Margono Wisanto (Yayasan Azhar Amanaa Yogyakarta, 2023)
This research is a qualitative research method of literature (library research), and data analysis using a thematic interpretation approach. This study aims to determine the interpretation of Q.S. Yusuf verses 46-60 and the values of disaster education implied in Q.S Yusuf 46-60. This study resulted in the story of Yusuf related to the disaster verses 46 to 60. The verses 46-60 are connected with the segment of Yusuf's story contained in the following sections: The interpretation of Yusuf's dream to the king's dream, Yusuf was released from prison, Yusuf was appointed as treasurer of Egypt, and the meeting Joseph with his brother. Disaster education in the story of Yusuf is found in two things related to disaster. These two things are the stages of disaster preparedness and disaster emergency. The preparedness stage fosters a careful, thorough, and anticipatory attitude. The stage of disaster emergency fosters an attitude of concern.